Identifikasi Anggota dalam Penempatan pada Struktur Organisasi menggunakan Metode Profile Matching - Ahmadi Ahmadi; Sarjon Defit; Jufriadif Na’am (Ikatan Ahli Informatika Indonesia (IAII), 2018)
The organization of a political party is one organization that must have an organizational structure. Each cadre who sits in the structure must have skills that match his field. The goal is for the organization to grow better. For each cadre to occupy the appropriate structure, identification must be performed. The method used to identify is Profile Matching on the data of each prospective member. Based on the test results obtained cadre with a special aspect of 60% and the general aspect of 40% is the right one. Then this method is suiTabel to be used in identifying cadres who will occupy positions in organizational structure.